Fatores controladores das concentrações de mercúrio (Hg) em organismos aquáticos costeiros da região semiárida brasileira - Moura, Victor Lacerda (2023)
Mercury (Hg) is naturally present in trace and ultra-trace concentrations, primarily emitted by volcanic and geothermal sources. However, human activities are contributing to increase the levels of this contaminant in ecosystems. Mercury's propensity for bioaccumulation and long tissue residence time leads to an accumulation of Hg in organisms. Other factors, such as biological and ecological considerations, could also increase Hg concentrations. In addition, environmental factors may also affect contaminant concentrations in biota. Despite several studies that have stressed the significance of these factors, little attention has been paid to the semiarid regions compared to other climatic zones. The objective of this study was to explore the impact of environmental, biological, and ecological characteristics on the variation of Hg concentrations in organisms inhabiting an estuary in the semiarid coastal region of Brazil. Samples were collected from water, sediment, and biota from the Jaguaribe river estuary, as well as from benthic organisms in the Icaraí beach coastal zone. The sampling in Jaguaribe river was conducted at seven points within the estuarine area during both rainy and dry periods, except for the aquatic fauna. At Icaraí beach, we collected five species of batoid fish. We measured hydrochemical parameters and quantified Hg in samples from the Jaguaribe River, and we measured the concentrations of dissolved and particulate Hg in the water samples. On Icaraí beach, we conducted total Hg, MeHg, and stable isotope quantification analyses to comprehend the significance of biological, ecological, and environmental factors in the accumulation of Hg in these organisms in each study area. The results from both study areas reveal the significant impact of biological and ecological factors on the levels of Hg found in the biota, particularly in batoid species. In terms of environmental aspects, a notable Hg concentration variation was observed along the saline gradient in the Jaguaribe river estuary. Regions with greater marine influence demonstrated elevated Hg concentrations and a faster accumulation rate of the contaminant in the biota. Spatially, both sediment and water samples presented comparable outcomes indicating higher levels located further from the estuary. During various climatic seasons, water, sediment, and aquatic plant samples were compared, demonstrating that the levels of Hg in the dissolved fraction, consisting of chemical compounds with significant bioavailability, were higher in the water samples during the dry season. This finding was supported by observation of higher concentrations of Hg in floating and submerged macrophytes during the same period compared to the rainy season. The concentrations of Hg in both water and sediment suggest the possibility of Hg remobilization from sediment into the water column. Such remobilization is more likely to occur in environments with greater marine influence, particularly during the dry season. As a result, contaminant concentrations in its dissolved form are higher in areas under greater marine influence than in those under less influence, which explains the higher levels of Hg in biota near the mouth of the affected water bodies.